Fixed Point Theorems of Set-Valued Mappings in Partially Ordered Hausdorff Topological Spaces - Shujun Jiang; Zhilong Li; Shihua Luo (Abstract and Applied Analysis)
In this work, several fixed point theorems of set-valued monotone mappings and set-valued Caristi-type mappings are proved in partially ordered Hausdorff topological spaces, which indeed extend and improve many recent results in the setting of metric spaces.